Implementing Eclectic Method for ELT through Distance Learning during the Covid-19 Pandemic - Irwandi Irwandi (Educatio, 2020)
This article argues that teaching English through distance learning during the Covid-19 pandemic requires an appropriate teaching method. This is since English language teaching (ELT) is not only aimed at guiding learners to master language skills, but also to learn independently and have a positive attitude towards learning English. To achieve this goal, this article promotes the implementation of the eclectic method to ELT for Junior and Senior High School learners through distance learning. Through the library research method, this research discovers the concept of distance learning, the characteristics of the eclectic method and its application strategy. Five main strategies are proposed for applying eclectic method, namely providing meaningful learning activities, finding eclectic features in various language teaching methods, applying contextual learning, giving various assignments, and providing differentiated feedback. It is concluded that beside to mediate the various language teaching methods with their strengths and weaknesses, this method also becomes a vehicle to lead the learners to learn English language independently. In brief, the eclectic method is feasible for English language teaching through distance learning during the Covid-19 pandemic.